Examining the Smoking Levels of Junior High School Students in Semarang City, Indonesia - Besar Tirto Husodo; Novia Handayani; Kusyogo Cahyo; Nurhasmadiar Nandini (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2020)
Background: The prevalence of active smokers in Indonesia remains high. Global Adults Tobacco Survey (GATS) on 2011 stated that Indonesia has the highest number of active smokers (67% male and 2.7% female). National Health Indicator Survey 2016 showed the number of male adolescent who smoke was 54.8%. The aim of this study was to examine the smoking levels of junior high school students in Semarang City in order to arrange improvement in behavioral changes through identifying the patterns of adolescent’s smoking behavior.Methods: This study used cross sectional study design. Samples were selected with simple random sampling technique, and 160 smokers who were junior high school students were obtained from 16 sub-districts in Semarang City. Data was analyzed using univariate and bivariate analysis.Results: The result showed that the majority of the respondents were light smokers (90.0%) who smoke <5 cigarettes/day. The chi square test showed that pocket money to buy cigarettes (p=0.011) and the social interaction pattern (p=0.026) have correlation to students’ smoking levels.Conclusion: Most students start to smoke at the age of less than 12 years old with light smoking degree. It is correlated with the pocket money to buy cigarettes and the social interaction pattern.